2021
DOI: 10.1021/acsami.1c12199
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Benefit between Cu(II) and Polydopamine for Improving Photothermal–Chemodynamic Therapy

Abstract: Combination therapy has attracted extensive interest in alleviating the shortcomings of monotherapy and enhancing the treatment efficacy. In this work, hollow mesoporous silica nanoparticles (HMSNs) play the role of nanocarriers in the delivery of Cu­(II)-doped polydopamine (PDA), termed as HMSNs@PDA-Cu, for synergistic therapy. PDA acts as a traditional photothermal agent to realize photothermal treatment (PTT). Chemodynamic therapy (CDT) is realized by the reaction of Cu­(II) with intracellular glutathione (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…When either laser or ultrasound irradiation was applied, CPM-treated cells showed stronger fluorescence intensity ( Figure 3C ), suggesting that both laser irradiation and ultrasound promoted ROS production. This result may be caused by ultrasound-enhanced mitochondrial Ca 2+ overload and laser-promoted CDT ( Zhang et al, 2021 ). As anticipated, the CPM + US + L group showed the strongest green fluorescence compared to the CPM + US and CPM + L groups, suggesting the superiority of the combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…When either laser or ultrasound irradiation was applied, CPM-treated cells showed stronger fluorescence intensity ( Figure 3C ), suggesting that both laser irradiation and ultrasound promoted ROS production. This result may be caused by ultrasound-enhanced mitochondrial Ca 2+ overload and laser-promoted CDT ( Zhang et al, 2021 ). As anticipated, the CPM + US + L group showed the strongest green fluorescence compared to the CPM + US and CPM + L groups, suggesting the superiority of the combination therapy.…”
Section: Resultsmentioning
confidence: 99%
“…[27] This further verified the formation of Schiff base between DAC and PDA. The highresolution scan XPS spectrum of Cu 2p (Figure 2e) displayed two Cu + characteristic peaks at 933.2 and 952.7 eV, [28,29] and other two peaks were associated with iodine (I) ion. The spectrum in electron paramagnetic resonance (EPR) also showed Cu + signals at 3353-3364 G (Figure 2f).…”
Section: Fabrication and Characterization Of Dac@pda/cu Membranementioning
confidence: 99%
“…These results suggested that PAM hydrogel, NIR laser irradiation and 0.5 mM H 2 O 2 had no antibacterial effect, and the photothermal effect of 150 μg/mL PDA was not enough to achieve antibacterial ability. [43][44][45]55 Compared with the PDA− PAM + NIR group, the FePDA−PAM + NIR treatment showed an obvious PTT antibacterial property (29.9%) due to the stronger absorbance and photothermal heating ability of FePDA. In the presence of H 2 O 2 , the FePDA−PAM hydrogel possessed a relatively better antibacterial effect (40.7%), which might be attributed to the ROS produced from FePDA effectively sterilizing bacteria by damaging cellular membranes, proteins, and DNA.…”
Section: 5mentioning
confidence: 99%
“…Fortunately, many studies have been reported on the acceleration of DA polymerization by reactive oxygen species (ROS) generated by metal ions and hydrogen peroxide (H 2 O 2 ). , It is worth noting that these transition metal ions (e.g., Fe 3+ , Cd 2+ , Cu 2+ , Ag + , Mn 2+ , Ni 2+ , etc.) can be assembled into the network structure of PDA in the polymerization process by chelating with catechol and/or imine groups and show the Fenton or Fenton-like activity for the conversion of exogenous and endogenous H 2 O 2 to the highly toxic hydroxyl radicals ( • OH), which can cause severe oxidative damage for chemodynamic therapy (CDT) of wound bacterial infection . For examples, Zhou et al prepared a novel divalent ion cross-linking alginate polyacrylamide hydrogel, which showed a spectrum of antibacterial activity and the ability to accelerate wound closure .…”
Section: Introductionmentioning
confidence: 99%